Congenital Transmission of Toxoplasma gondii After Experimental Reinfection With Brazilian Typical Strains in Chronically Infected Sheep - Chiebao, Daniela Pontes; Pena, Hilda Fátima; Passarelli, Danielle; Santín, Thiago; Pulz, Lidia Hildebrand; Strefezzi, Ricardo Francisco; Sevá, Anaiá Paixão; Martins, Camila Marinelli; Lopes, Estela Gallucci; Grisi Filho, José Henrique Hildebrand; Gennari, Solange Maria; Soares, Rodrigo Martins (Frontiers in Veterinary Science, 2019)
Toxoplasma gondii is a cause of congenital diseases, miscarriages and stillbirths in production animals. In Brazil, non-archetypal genotypes of the parasite may be related to severe disease. Experimental infection with T. gondii was studied in sheep to analyse congenital transmission-related parameters in reinfections with different Brazilian parasite strains. Thirteen T. gondii-seronegative sheep were orally infected with 2x103oocysts for the primary infection: G1 (4 animals) were inoculated with TgCatBr71 strain (Type BrI genotype) and G2 andG3 (5 and 4 animals, respectively) withTgCatBr60 strain (Type BrIII genotype). After chronification of infection, the animals were impregnated. A second infection was performed after 60 days of gestation. TheG1 andG3 animals were inoculated withTgCatBr60BrIII and the G2 animals withTgCatBr71 BrI oocysts. The effects of reinfection were compared with a control group (5 animals) through physical examination, ultrasound imaging and serology. Ovine experimental infections were evaluated using mouse bioassays, molecular analysis, serological tests, histopathology and immunohistochemistry. No abortions occurred; a seropositive lamb and a mummified foetus from G2-BrIIIxBrI were produced. The vertical transmission rate detected in lambs from chronically infected sheep was 31.6% (6/19). It is demonstrated that reinfection and subsequent congenital transmission occured in one sheep with a primary Brl infection challenged with BrIII genotype of T. gondii. In a twin pregnancy from G2-BrIIIxBrI, congenital transmission from a latent infection was detected in both lambs. Congenital transmission could not be tracked in three lambs. Overall, previous T. gondii infection may fail to protect against congenital transmission from a reinfection and primary infection induced insufficient protection against vertical transmission which must be taken into account in decision-making for the use of seropositive animals as breeders. Similar trials with larger groups and contemplating host cellular immune response studies should be conducted to evaluate the actual impact of T. gondii reinfection involving different strains in sheep.